Effect of nodes excised from different position of Gynura procumbens mother stock plant on reduction of microbial contamination and increasing in vitro explant survival - Aziz, Nurul Shaffiqqa (2018)
Gynura procumbens belongs to the Asteraceae family. This plant grows naturally in tropical Asia countries such as Malaysia and Indonesia. Its common name is longevity spinach or ‘sambung nyawa’ in Malay. It is a small herbaceous plant with ovate-elliptic leaves and is commonly used as a medical plant. Its leaves contain bioactive compound that can cure several diseases such as cancer, hypertension, diabetes mellitus, kidney discomfort, and inflammation. The common propagation method of this plant is through stem cutting but the number of cuttings that can be excised from a whole plant for propagation is very limited. Therefore, another alternative for mass propagation of Gynura procumbens plants is through tissue culture method. Currently there is no in vitro culture research carried out on Gynura procumbens. This initial study is aimed to reduce microbial contamination and to induce shoot generation from node cultures of Gynura procumbens. The experiment is carried out at In Vitro Laboratory, Department of Agriculture, Universiti Putra Malaysia (UPM) to determine the nodal segment which is less microbial contamination and to evaluate the best concentration and immersion time of explant in Clorox in reducing microbial contamination. The experiment is conducted using Completely Randomised Design (CRD). It was observed that no significant difference was observed on percentage of fungal and bacterial contamination, explants browning and explant survival by the nodes excised from different position on the mother stock plant. Fungal and bacterial contamination in these explants ranged between 16% to 73% and 6% to 20% respectively. The explant survival ranged between 80% and 90% in these explants indicating that these explants are good material for initiating culture establishment and later propagule multiplication.